2015
DOI: 10.1155/2015/530319
|View full text |Cite
|
Sign up to set email alerts
|

Antineutrophilic Cytoplasmic Antibody Positive Vasculitis Associated with Methimazole Use

Abstract: ANCA-associated vasculitis (AAV) is a rare and potentially life threatening complication associated with antithyroid drug use. It is more commonly reported with propylthiouracil, with fewer cases reported with methimazole use. We present the case of a 55-year-old man with toxic multinodular goiter which was treated with methimazole for 6 months. He developed ANCA positive leukocytoclastic vasculitis with hemorrhagic and necrotic bullous lesions of lower extremities. The vasculitis was initially thought to be s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…Kawachi et al [10] reported the first case of MMI-induced antineutrophil cytoplasmic antibodies (ANCA)-associated cutaneous vasculitis in 1995. The following cases confirmed the validity of the proposed pathogenesis which is related to the stimulation of a particular immune processes, leading to the production of ANCA [11, 12, 13, 14, 15, 16]. However, Kanat et al [17] reported a case with recurrent hyperthyroidism who developed ANCA-negative cutaneous small-vessel vasculitis after taking MMI (20 mg daily) for 1 week.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Kawachi et al [10] reported the first case of MMI-induced antineutrophil cytoplasmic antibodies (ANCA)-associated cutaneous vasculitis in 1995. The following cases confirmed the validity of the proposed pathogenesis which is related to the stimulation of a particular immune processes, leading to the production of ANCA [11, 12, 13, 14, 15, 16]. However, Kanat et al [17] reported a case with recurrent hyperthyroidism who developed ANCA-negative cutaneous small-vessel vasculitis after taking MMI (20 mg daily) for 1 week.…”
Section: Discussionsupporting
confidence: 57%
“…It is also interesting to note that most cases with MMI-induced leukocytoclastic vasculitis took many months to develop after the initiation of the medication. However, this is only true in individuals with no history of PTU exposure [12, 13]. In contrast, 4 reported cases [11, 14, 15, 17], who had a history of prior PTU administration, developed MMI-induced cutaneous vasculitis over a shorter period of exposure (i.e., approximately 1 week).…”
Section: Discussionmentioning
confidence: 99%
“…Small-vessel vasculitis are evaluated under two headings either antineutrophil cytoplasmic antibody (ANCA) positive or ANCA negative. These antibodies are autoantibodies that target lysosomal enzymes of neutrophils and grouped as c-ANCA that is against proteinase, and p-ANCA that is against myeloperoxidase [4]. ANCA positive small-vessel vasculitis are classified under four groups as microscopic polyangiitis, Wegener's granulomatosis, Churg-Strauss syndrome, and drug-induced vasculitis [5].…”
Section: Discussionmentioning
confidence: 99%
“…2 In parallel, reports of methimazole-associated vasculitis have increased, with clinical manifestations ranging from cutaneous ulcers to pulmonary hemorrhage. [3][4][5][6][7][8][9] The incidence of ANCA-positive propylthiouracil-associated vasculitis is reportedly 39.2 times higher than in patients receiving methimazole. 3 Hydralazine, minocycline, and propylthiouracil are commonly prescribed medications known to cause positive ANA, P-ANCA, and MPO-ANCA test results, and vasculitic skin, kidney, and lung disease.…”
Section: Discussionmentioning
confidence: 99%
“…1,10 Cutaneous lesions include maculopapules, vesicles, purpura, bullae, and ulcers on the lower extremities, with hemorrhage and/or necrosis. 1,[4][5][6][7][8][9][10] Clinicians should exclude more common causes of these skin lesions, including infections, neoplasms, and primary vasculitides, and must be aware that drug-induced vasculitis can occur after several years on a medication. 1 One should perform an ANCA test and obtain a skin biopsy specimen for histologic evidence of vasculitis.…”
Section: Discussionmentioning
confidence: 99%